Classical and non-classical thyroid hormone intracellular pathways involved in T lymphoma growth - Barreiro Arcos, María Laura (2014)
Fil: Barreiro Arcos, María Laura. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina